Does School Climate Matter for Job Satisfaction? The Mediating Role of Teachers’ Self-Efficacy and Work Engagement - Meditamar, Muhd. Odha (Jurnal Pedagogi dan Pembelajaran, 2024)
Teacher job satisfaction is crucial in supporting the achievement of individual and organizational performance in education. However, in the context of education in Indonesia, there is a lack of research specifically exploring how school climate affects teacher job satisfaction, particularly considering the role of self-efficacy and work engagement as mediating variables. This study aims to analyze the mediating role of self-efficacy and work engagement in the relationship between school climate and teacher job satisfaction. The study uses a cross-sectional survey design involving 208 senior high school teachers (44.13% male, 59.13% female; average age = 37.96, SD = 8.34). Data were collected using the Minnesota Satisfaction Questionnaire (MSQ), School Climate Survey, Teachers’ Self-Efficacy Scale, and Utrecht Work Engagement Shortened Version (UWES-9). Data analysis was conducted using Structural Equation Modelling - Partial Least Squares (SEM-PLS) to test the hypotheses. The results indicate that school climate significantly influences teacher job satisfaction through the mediation of self-efficacy. Furthermore, work engagement also serves as a significant mediator in this relationship. These findings contribute to efforts to enhance teacher job satisfaction, showing that a positive school climate can foster improvements in self-efficacy and work engagement, which, in turn, enhances teacher job satisfaction. Therefore, it is essential to create a supportive school climate to improve teachers' overall well-being.